Role of Fe Impurity Reactions in the Electrochemical Properties of MgFeB2O5 - Tacconis, Camilla; Dey, Sunita; McLaughlin, Carson D.; Sougrati, Moulay Tahar; O’Keefe, Christopher A.; Mikulska, Iuliia; Grey, Clare P.; Dutton, Siân E. (Chemistry of materials, 2025)
We investigate magnesium–iron pyroborate MgFeB2O5 as a potential cathode material for rechargeable magnesium-ion batteries. Synchrotron powder X-ray diffraction and Mössbauer spectroscopy confirm its successful synthesis and iron stabilization in the high-spin Fe(II) state. Initial electrochemical testing against a lithium metal anode yields a first charge capacity near the theoretical value (147.45 mAh·g–1), suggesting MgFeB2O5 as a promising cathode candidate. However, multimodal analyses, including scanning electron microscopy energy-dispersive X-ray (SEM-EDS) analysis, operando X-ray absorption near edge spectroscopy (XANES), and Mössbauer spectroscopy, reveal the absence of any Fe redox reactions. Instead, we propose that the source of the observed capacity involves the irreversible reaction of a small (4–7 wt%) Fe metal impurity. These findings highlight the need for diverse characterization techniques in evaluating the performance of new Mg cathode materials, since promising initial cycling may be caused by competing side reactions rather than Mg (de)intercalation.